The effect of reception quality on the selection of setting zone / Muhammad Aniq Amsyar Azmin ... [et al.]. - Azmin, Muhammad Aniq Amsyar; Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Abu Kassi, Nurul Ain; Mazaulan, Mardiana; Syed Mud Puad, Sharifah Maimunah; Shari, Maisarah (2024)
In volleyball, reception is the first action, followed by setting. The quality of reception is crucial for winning a volleyball match because it can affect setting zone selection. This study aimed to determine the effect of reception quality on the selection of setting zones in volleyball. A total of 64 matches from the top four teams in two tournaments were selected: Sooka Super Series Volleyball 2022 (n = 32) and the PKNS Invitational Volleyball League 2023 (n = 32). Reception quality was categorized using a 5-point numerical rating scale, ranging from 0 to 4 (0 = no reception/error, 1 = poor, 2 = average, 3 = good, 4 = excellent). Next, setting zone selection was categorized according to the consequent attacking areas in zones 1, 2, 3, 4, 5, and 6. Results showed that out of 24 variables of reception quality on the setting zone between Sooka Super Series Volleyball 2022 and the PKNS Invitational Volleyball League 2023, there are 14 variables that had significant differences (p < 0.05). The Sooka Super Series Volleyball had higher scores in reception quality (4), while the PKNS Invitational Volleyball League 2023 had higher scores in reception quality (3). This difference is attributed to the presence of professional teams that have raised the level of play to a higher level in terms of reception. This is likely due to their technique of keeping their arm platform parallel to the floor during contact with the ball. In both tournaments, setting zone 4 was the most frequently selected setting zone. Thus, zone 4 is considered the best option for attack zones due to the ample space it provides for attackers to perform spikes.